2022
DOI: 10.1371/journal.pone.0279315
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sphingolipid abnormalities in neurodegenerative diseases

Abstract: Background In recent years, there has been increasing evidence that several lipid metabolism abnormalities play an important role in the pathogenesis of neurodegenerative diseases. However, it is still unclear which lipid metabolism abnormalities play the most important role in neurodegenerative diseases. Plasma lipid metabolomics (lipidomics) has been shown to be an unbiased method that can be used to explore lipid metabolism abnormalities in neurodegenerative diseases. Plasma lipidomics in neurodegenerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Therefore, we are interested in determining whether RBCs contribute to the AD pathogenesis. Previous studies have reported decreased S1P levels in AD tissues and plasma [39,40]. S1P protects neuronal cells from apoptosis [41], notably in response to A [42].…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, we are interested in determining whether RBCs contribute to the AD pathogenesis. Previous studies have reported decreased S1P levels in AD tissues and plasma [39,40]. S1P protects neuronal cells from apoptosis [41], notably in response to A [42].…”
Section: Introductionmentioning
confidence: 89%
“…In vivo studies suggest that osteopontin (CSF and blood) [97,98], serpins (CSF and blood) [85], sphingolipids and lysophospholipids (blood) [99], and serum amyloid A (CSF) [76] are altered in LBD disease cohorts compared to controls and therefore may have neurobiological relevance to LBD, or at least neurodegeneration more broadly. Protein glycosylation profiles might predict conversion to DLB versus PD clinical disease in people with idiopathic REM sleep disorder [32].…”
Section: Other Inflammatory Molecules Measured Postmortem and In Vivomentioning
confidence: 99%
“…Blood levels of cytokines, and possibly other biomarkers of interest, are affected by diurnal variation [157]. Only a handful of identified studies, however, report standardizing collection time, with samples for inflammatory molecule analysis taken in the morning or fasted (likely a morning sample) [33,62,67,72,76,78,[99][100][101]156]. As mentioned above, the sensitivity of the assays used may be too low to detect molecules of interest, particularly when comparing older studies to those using more advanced detection methods or comparing different assay platforms; therefore, conclusions that can be drawn about their absence are limited [158,159].…”
Section: Limitations Of In Vivo Studiesmentioning
confidence: 99%
“…This lipid species is related to the metabolic pathway of glucosylceramide, which is linked to PD [ 209 ]. Another study used LC-MS/MS to evaluate plasma lipidomics in individuals with different neurodegenerative diseases, including idiopathic PD, dementia with LB and multiple system atrophy, as synucleinopathies, and Alzheimer’s disease and progressive supranuclear palsy, as tauopathies [ 228 ]. In this study, the authors found that the plasma levels of sphingosine-1-phosphate (which seems to have a neuroprotective role against aggregate formation) were lower, and those of monohexylceramide and lactosylceramide (which seem to be involved in neuroinflammation and neuronal cell death) were higher in the neurodegenerative disease groups, compared with the healthy controls, supporting the idea that abnormal sphingolipid metabolism has a key role in neurodegeneration [ 228 ].…”
Section: Lipidomics As a New Tool To Identify Biomarkers In Parkinson...mentioning
confidence: 99%